Who cares about rural libraries? Tracking a neglected research topic in library and information science - Sánchez-Pita, Fernando; Cabezas-Clavijo, Álvaro (Library & information science research, 2025)
Rural libraries have historically received minimal attention from the academic community despite their critical role in providing access to information, education, and recreational resources in rural areas. The state of research on rural libraries was examined. Drawing on a corpus of 159 publications from the Web of Science database covering the period from 1970 to 2023, research on rural libraries remains limited in both volume and influence. The field demonstrates low interconnectivity with other disciplines, with approximately 70 % of publications appearing in Library and Information Science (LIS) journals. Additionally, the visibility of this research is low, with merely 8.6 % of articles published in top-tier journals based on their impact factor. •Rural libraries are rarely studied and have limited connections to other disciplines.•There is no structured and cohesive scientific community around this subject.•This field is characterized by the dispersal of topics and a disjointed network of authors.•A retrospective descriptive analysis is conducted on publications related to the subject.•This topic can be seen as an opportunity beyond library and information science.